SWOT Analysis as a Strategy for Enhancing Nursing Officer Performance Through Leadership, Rewards, and Facilities - Albert Muna; Usman Rianse; Samdin Samdin; Adius Kusnan; Nur Juliana (AIBPM Publisher, 2025)
RSUD Bahteramas Kendari, as a referral hospital, plays an essential role in providing health services. This study aims to analyze the strengths, weaknesses, opportunities, and threats related to the role of leadership, rewards, and facilities on the performance of nursing staff in 2024 and strategies for optimizing service satisfaction. This study used a qualitative descriptive method. The 20 respondents were selected using the snowball sampling technique. Data collection through interviews, observation, and documentation was analyzed using SWOT to identify internal and external factors. The results showed strengths in effective leadership (score 2,11), competitive reward systems, and modern health facilities. Weaknesses include a lack of leadership training (score 1,90) and compensation transparency, which needs to be improved. Externally, opportunities include adopting new technology and cooperation with educational institutions (score 1,37). Threats include competition from other hospitals and government policy pressure (score 1,44). The resulting strategy is quadrant II of the diversification strategy, which utilizes opportunities to overcome weaknesses. Optimizing leadership training, increasing rewards transparency, taking advantage of technological possibilities, and promoting educational cooperation are recommended to improve nurse performance and service satisfaction.